Prenatal ultrasound utilization and associated factors among pregnant women attending antenatal care in south Wollo zone public hospitals, north east, Ethiopia, 2023 - Susu, Belay; Temesgen, Kibir; Ayalew, Sindu; Yibeltal, Selam; Emagneneh, Tadele; Yesuf, Adem; Mulugeta, Chalie (Frontiers in Digital Health, 2025)
BackgroundPrenatal ultrasound (US) is essential in antenatal care worldwide and offers significant benefits for maternal and neonatal health. It should be a standard procedure in low- income countries. However, its utilization remains poor in nations such as Ethiopia.ObjectiveThis study aimed to assess the use of prenatal ultrasound and associated factors among pregnant women who attended antenatal care in South Wollo Zone Public Hospitals, Northeast Ethiopia, in 2023.MethodAn institution-based cross-sectional study was conducted among 590 pregnant women from December 30, 2022, to February 28, 2023, in selected South Wollo Zone Public Hospitals. The data were coded, cleaned, and entered into Epi-Data version 4.6 and subsequently exported to SPSS version 26 for analysis. The strength of the association between the dependent and independent variables was presented as odds ratios (ORs) at a 95% confidence interval (95% CI), with a P-value of less than 0.05 according to multivariable logistic regression.ResultsThe prevalence of prenatal ultrasound utilization was 62.8% [95% CI: 58.7%–66.8%]. The significant factors associated with utilization included urban residency (AOR = 4.82, 95% CI: 2.99–8.03), mothers’ knowledge (AOR = 7.36, 95% CI: 4.06–13.32), educational status above primary (AOR = 2.10, 95% CI: 1.09–4.05), medical illness (AOR = 3.03, 95% CI: 1.64–5.59), government employment (AOR = 4.05, 95% CI: 1.70–9.64), and private employment (AOR = 2.34, 95% CI: 1.58–7.05).ConclusionThe proportion of patients who underwent prenatal ultrasound was lower than the WHO recommendation. The factors most significantly associated with ultrasound utilization were women's knowledge, urban residency, educational status, medical illness, and occupation. Therefore, the author recommended for health care providers educating mothers on the purposes of obstetric ultrasound and including a prenatal ultrasound screening as part of antenatal care is needed.